INCREASING CANCER AWARENESS THROUGH THE FUZZY DELPHI METHOD: EFFECTIVE STRATEGIES FOR THE COMMUNITY - Ahmad Saharrudin Mat Akir; Engku Mardiah Engku Kamarudin; Noor Syamilah Zakaria, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study examines the impact of personal, behavioral, and environmental factors on cancer awareness in the community using the Fuzzy Delphi method. Expert surveys were conducted, achieving high consensus rates (87-91%) across all domains. The analysis revealed that outcome expectations (defuzzification value: 0.95455) were the most significant personal factor, while supportive behavior (0.96364) was the most crucial behavioral aspect. In the environmental domain, health infrastructure and community support (both 0.91818) were equally important. The study emphasizes the need for holistic approaches in health promotion, highlighting the complexity of health determinants. It provides valuable insights to assist policymakers and healthcare professionals in designing more comprehensive and effective cancer awareness initiatives. Furthermore, this research establishes a foundation for future longitudinal studies, cross-cultural assessments, and the development of integrated health promotion strategies that address multiple factors simultaneously.